Double-Layered Lateral Meniscus Accompanied by Meniscocapsular Separation - Aki Fukuda; Akinobu Nishimura; Shigeto Nakazora; Ko Kato; Akihiro Sudo (Case Reports in Orthopedics, 2015)
We report an extremely rare case of double-layered lateral meniscus accompanied by meniscocapsular separation. The upper accessory meniscus was connected with the posterior horn and middle segment of the lower normal meniscus and was more mobile than the lower normal meniscus. A meniscocapsular separation was evident at the overlapping middle segment. Clinical symptoms were significantly improved by the resection of the upper accessory meniscus and the repair of the meniscocapsular separation. Careful arthroscopic analysis of other associated pathologies together with this rare abnormality was needed to achieve clinical improvement.